Cirque du freak - Shan, Darren (Boston : Little, Brown, 2001)
Two boys who are best friends visit an illegal freak show, where an encounter with a vampire and a deadly spider forces them to make life-changing choices.
"First published in Great Britain by Collins in 2000 ... London"--T.p. verso.
Sequel: The vampire's assistant.
Booklist.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
7.1.
Keywords: Best friends -- Fiction; Conduct of life -- Fiction; Freak shows -- Fiction; Friendship -- Fiction; Horror stories; Spiders -- Fiction; Vampires -- Fiction; Conduct of life -- Fiction; Friendship -- Fiction; Horror fiction; Sideshows -- Fiction; Spiders -- Fiction; Vampires -- Fiction